Implementasi Environtment, Occupational Health And Safety, Stakeholder’s Engagement Dan Corporate Governance Dalam Kaidah Pertambangan Terhadap Pembangunan Berkelanjutan - Sukmawan Nurhamda (Jurnal Impresi Indonesia, 2025)
This study aims to find out how to implement the environment, occupational health and safety, stakeholder engagement and corporate governance in mining principles towards sustainable development.This study uses the Social Environment (SE) variable and the Environtment, Occupational Heatlh, Stakeholder's Engagement, Good Corporate Governance (GCG) variables as a measuring tool to reduce negative impacts with optimal results for the achievement of the principles of Good Mining Practice. The sample used in this study is 3 (three) mining sector companies that have successfully implemented the principles of Good Mining Practice. The data obtained were analyzed using qualitative analysis techniques. The results of this study show that the implementation and integration of commitments to sustainable development, especially to the SDGs guidelines, is consistently carried out by ANTAM, BRMS, and VALE. However, it should be noted that even though viewed from the SDG integration data, companies tend to focus more on several SDGs